Response of seeds and growth of Cassia fistula L. seedlings to immersion with different periods and concentrations of sulfuric and gibberellic acid - Rand Khalid Yones; Shahla Abd Alrazaq Basher (Journal of Kerbala for Agricultural Sciences, 2025)
This study was conducted in the nursery of the Forestry Department, College of Agriculture and Forestry/University of Mosul. On Cassia fistula seeds during 4/10/2023 to 10/15/2023, they were treated with sulfuric acid at two concentrations 98% and 50% for different periods (0, 5, 10, 15, 20 minutes) and then immersed in gibberellic acid at concentrations (0, 500, 1000 mg. L-1). The results showed that the 20-minute immersion treatment with sulfuric acid recorded the highest averages for the traits (germination percentage, germination speed, seedling height, dry weight of the vegetative group). The study also showed that sulfuric acid at a concentration of 98% was superior to 50% in the characteristics (germination percentage, germination speed, seedling height, number of leaves, and dry weight of the vegetative group), and gibberellic acid at a concentration of 500 mg. L-1 had a positive effect and recorded the highest averages in (germination percentage, germination speed, seedling height, number of leaves, dry weight of the vegetative group).